The Performance of Public Junior High School Education Personnel in Tulang Bawang, Lampung - Rian, Yuriansyah; Riswandi, Riswandi; Rini, Riswanti; Handoko, Handoko (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to comprehensively analyze the impact of principal leadership, work motivation, and work discipline on the performance of educational staff in state junior high schools within Tulang Bawang Regency. The research employs an ex post facto quantitative approach with a population of 153 educational staff members. Through proportional random sampling, 111 participants were selected for the study. Data collection involved the use of questionnaires, and subsequent analysis included prerequisite regression tests such as normality, heteroscedasticity, multicollinearity, and linearity. The findings reveal noteworthy outcomes: (1) Principal leadership significantly and positively influences the performance of educational staff. (2) Work motivation exhibits a positive and significant impact on the performance of educational staff. (3) Work discipline similarly demonstrates a positive and significant influence on educational staff performance. (4) Simultaneously, principal leadership, work motivation, and work discipline collectively exert a positive and significant influence on the performance of educational staff. This research contributes valuable insights to educational management literature by establishing the crucial role of leadership, motivation, and discipline in enhancing the performance of educational staff. Based on these findings, recommendations are made for educational institutions to focus on strengthening these factors to optimize staff performance, ultimately improving overall educational quality.